Data Sharing in the Internet of Medical Things: Between the Data Act and the EHDS - F. Casarosa; F. Gennari (European Journal of Risk Regulation)
Healthcare systems are increasingly exploiting the advantages of Internet of Things technologies: cloud-connected devices with perceptive sensors can gather very accurate health data from people even if they do not get to the hospital or private clinics. For potential innovators of new medical IoT devices, the legal framework applicable was until now limited to the application of the General Data Protection Regulation and the Medical Devices Regulation.